The FcRn from gene to protein and function: comparison between species - Ortiz-Alegría, Luz Belinda; Xicoténcatl-García, Lizbeth; Cañedo-Solares, Irma; Rico-Torres, Claudia Patricia; Gómez-Chávez, Fernando (Frontiers in Immunology, 2025)
Immunoglobulin Fc receptors are crucial molecules in immunological processes that help maintain homeostasis following internal or external stimuli. Most of the specific gamma recognition molecules (FcγRI, II, and III) are known for their roles in phagocytosis and cellular cytotoxicity against various pathogens and transformed cells and in regulating the humoral immune response. Within this family of IgG Fc receptors, there is a structurally similar receptor with different functions: the so-called neonatal receptor for the Fc fraction of IgG, or FcRn, which is primarily associated with IgG and albumin homeostasis, the transfer of immunity from mother to offspring, and the regulation of the immune response in mammals. Therefore, this molecule could be considered “the regulator and transporter of the main blood proteins” from the blood vessels and the lumen of the mucosa to the tissues of the newborn and neonate, through the epithelium and endothelium. It may act as a trans-tissue and interindividual “protector,” as it mediates the transfer of IgG antibodies to the sites where they are needed. Additionally, it regulates plasma albumin and IgG concentrations, contributing to the balance of body fluids. Although there is abundant literature on this receptor, some phenomena remain unexplored or poorly understood. In particular, the variations in its functions across different cell types and between species, how they influence IgG and albumin levels in various body fluids, and the pathways involved in immunity transmission need further investigation. In this paper, we present a comprehensive review of original research articles and analyses focused on the gene, mRNA, and protein composition of the FcRn, with the aim to compare the genetic, structural, and functional characteristics in different mammalian species, focusing on its role in immunity and homeostasis, as well as the ontogeny and phylogeny of the FcRn.